APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN MANAGEMENT OF INFORMATION RESOURCES AND SERVICES IN KADUNA STATE TERTIARY INSTITUTIONS’ LIBRARIES KADUNA-NIGERIA - Ridwan, Sani Murtala (European Scientific Journal, ESJ, 2015)
The application and diffusion of information and communication technology cannot be viewed in isolation from development in telecommunication technology. Innovation in computer and telecommunication technology have resulted in major changes in basic library operations as well as managing information in different offices and organization, such as circulatory reference services, cataloguing and classification, collection development (ordering and acquisition). However, the innovations have prompted many organizations to employ the use of ICT devices to further manage information and records of the organization. On this note, many organizations, now adopt the use of computer systems, database management systems, development of network systems to create, store, preserve, secure and use information for effective decision making in the organization. This paper highlights the prospects and problems of I.C.T in Kaduna state tertiary institutions’ libraries. Recommendation for functional I.C.T. in Kaduna state tertiary institutions’ libraries have also been given.